ANALISIS TINGKAT PEMAHAMAN DAN KESIAPAN PENGELOLA UMKM DALAM IMPLEMENTASI LAPORAN KEUANGAN BERBASIS SAK-EMKM SERTA DAMPAKNYA DALAM KEMUDAHAN AKSES KELEMBAGA KEUANGAN - Yulis, Yul Emri; Irwan, M.; Andriani, Rina (Buletin Studi Ekonomi; VOLUME.27.NO.2.TAHUN.2022DO - 10.24843/BSE.2022.v27.i02.p08, 2022)
This research is a qualitative descriptive study that describes the level of understanding and readiness for implementing SAK-EMKM-based financial reports and their impact on easy access to financial institutions in Kecamatan Kuantan Tengah and Kecamayan Benai. Primary data was obtained from distributing questionnaires, while secondary data was obtained from the Ministry of Cooperatives and UMKM. The population in this study are UMKM managers in Kecamatan Kuantan Tengah and Kecamatan Benai, companies that are included in manufacturing companies on the Indonesia Stock Exchange for the period 2013-2015. Sampling was done through purposive sampling. Data analysis conducted in this research is descriptive statistical analysis The results of this study state that UMKM managers do not understand and are not ready to implement SAK-EMKM financial reports, and the impact of convenience for UMKM that have compiled financial reports in accessing financial institutions or getting credit for UMKM